Problem Based Learning to Improve Critical Thinking - Arifin, Egi Gustomo (Universitas Sebelas Maret, 2020)
curriculum has also changed, namely with a scientific approach. The criteria in this approach emphasize several aspects, including learning materials based on facts or phenomena that can be explained by logic, teacher explanations, student responses, and educative interactions between teachers and students, subjective thinking, encouraging and inspiring students to think critically, analytically, and accurately in identifying, understanding, solving problems, and applying learning materials.Teachers as educators must develop student's critical thinking skills. Aim of this study describes the concept of Problem Based Learning (PBL), components of critical thinking skills and the relationship of PBL with critical thinking skills. The results are problem-based learning can improve critical thinking through 5 phases, (a) orienting problems; (b) organize students to research; (c) assist group investigations; (d) develop and present the work; (e) analyze and evaluate the problem solving process.